2018
DOI: 10.1158/0008-5472.can-18-0365
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic BRAFV600E Governs Regulatory T-cell Recruitment during Melanoma Tumorigenesis

Abstract: Regulatory T cells (Treg) are critical mediators of immunosuppression in established tumors, although little is known about their role in restraining immunosurveillance during tumorigenesis. Here, we employ an inducible autochthonous model of melanoma to investigate the earliest Treg and CD8 effector T-cell responses during oncogene-driven tumorigenesis. Induction of oncogenic BRAF and loss of Pten in melanocytes led to localized accumulation of FoxP3 Tregs, but not CD8 T cells, within 1 week of detectable inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 52 publications
0
73
0
Order By: Relevance
“…Regulatory T cells (Tregs) are identified as immunosuppressive subset of CD4 + T cells (D. Wang, Quiros, et al, ) that represent about 4–5% of the whole CD4 + T‐cell population in normal conditions (Mougiakakos et al, ), and they work for preserving immune tolerance and suppressing autoimmune diseases (D. Wang, Quiros, et al, ). Tregs are identified as the prevailing T‐cell responders to the early tumors outpacing cytotoxic T lymphocytes (CTLs) during early tumor growth (Shabaneh et al, ). To maintain immune system in homeostasis, there is a tight regulation over Treg development (Y. Liu, Zhang, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory T cells (Tregs) are identified as immunosuppressive subset of CD4 + T cells (D. Wang, Quiros, et al, ) that represent about 4–5% of the whole CD4 + T‐cell population in normal conditions (Mougiakakos et al, ), and they work for preserving immune tolerance and suppressing autoimmune diseases (D. Wang, Quiros, et al, ). Tregs are identified as the prevailing T‐cell responders to the early tumors outpacing cytotoxic T lymphocytes (CTLs) during early tumor growth (Shabaneh et al, ). To maintain immune system in homeostasis, there is a tight regulation over Treg development (Y. Liu, Zhang, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…By using the NOD mouse model, Tang et al were able to show that, in vitro, expanded Tregs are capable of inhibiting autoimmune diabetes after adoptive transfer. 36 In human colorectal cancer, accumulation of Tregs within tumors is associated with metastasis. A phase I trial in humans with type I diabetes showed that a substantial proportion of adoptively transferred Tregs can survive long term and may maintain pancreatic endocrine function, providing a platform for the development of future clinical trials.…”
Section: In S I G Hts G Ained From Non -Tr Ans Pl Ant Pathologymentioning
confidence: 99%
“…In a mouse model of melanoma, for example, Tregs infiltrate the skin after tumor induction and lead to an increase in the Treg:CD8 + T cell ratios. 36 In human colorectal cancer, accumulation of Tregs within tumors is associated with metastasis. 37 Similarly, in the setting of some infections such as lymphocytic choriomeningitis virus, antigenspecific Tregs increase in the peripheral blood.…”
Section: In S I G Hts G Ained From Non -Tr Ans Pl Ant Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although tumour tissues are infiltrated by a large number of immune cells, it is still difficult to prevent the invasion and metastasis of tumour cells, suggesting that tumour cells can escape surveillance and killing by immune cells [10,11]. It is also discovered that tumour cells can induce differentiation of immune cells [12], for example, TAM2 macrophages and Tregs [13,14]. Therefore, further understanding of the interaction between tumour cells and immune cells provides us with the possibility of screening new targets.…”
Section: Introductionmentioning
confidence: 99%